64 Multisystem Inflammatory Syndrome in children, management in a peripheral setting. (11th October 2021) - Kelly, E; Jawad, M; Azam, M; Kalim, A
Abstract : Introduction: In the context of the Covid 19 Pandemic Multisystem Inflammatory Syndrome in Children (MIS-C) is an important new differential requiring consideration, this report describes 2 cases seen in a secondary paediatric centre setting. Case Description: Case 1: A 3 year-old boy presented with a four-day history of fever, malaise and decreased oral intake. The fever was persistent, it peaked at 40.8 C. Over 4 days he had had 2 vomits but no other symptoms. He had no significant medical history and no known history of Covid 19 disease. Physical examination revealed no source of fever. Case 2: A 14-month-old girl presented with a 1 day history of fever, malaise and decreased oral intake. She had no significant medical history and no known history of Covid 19 disease. No source of fever was evident on exam. Initial investigations included chest x-ray, urine culture, blood culture and throat/nasal swab for PCR for SARS CoV-2, all were negative. Their markers of inflammation were elevated and continued to rise with persistent fever, despite treatment with IV ceftriaxone. With no clear source of fever and no improvement, in consultation with the Infectious Diseases team in our tertiary referral hospital, we began treatment with intravenous immunoglobulin (IVIG), IV methylprednisolone and high dose aspirin for suspected MIS-C in Case 1, Case 2 was transferred to the tertiary centre for the same treatment at the ward level. With the IVIG infusion, all fever and symptoms resolved. An Echocardiogram was organised for each in the acute setting and repeated at 6 weeks, they demonstrated normal cardiac systolic and diastolic function with no evidence of significant coronary dilatation. Case Discussion: Though MIS-C is rare, with an incidence of 0.14% among children with SARS CoV-2 infection according to one Systematic Review (Hoang Et al. 2020), it is an important new differential which must be borne in mind in cases of fever with no clear source. Both of these cases had a negative PCR test for SARS CoV-2 and no history of Covid 19 disease. No serological testing for SARS CoV-2 was available in our hospital setting. But in accordance with RCPCH guidelines this does not exclude the diagnosis of MIS-C In previous studies as many as 71% of cases of MIS-C required PICU admission (Ahmed Et al., 2020), however not all are severely unwell and may be stable enough to be managed on a ward setting as described above.